The European Company. general editors, Dirk van Gerven, Paul Storm. - Gerven, Dirk van; Storm, Paul (Law practitioner series., 2008)
The European Company ('SE') is a legal entity offering a European perspective for businesses. Its purpose is to allow businesses that wish to extend their activities beyond their home Member State to operate throughout the EU on the basis of one set of rules and a unified management system. The book explains how to set up and organise a European Company, as well as setting out the text of the EC instruments (a Regulation and a Directive) serving as its legal basis, and a list of national implementing laws. This second volume reports on the countries which have legislated during 2005 and 2006. Divided into two sections, it first offers critical review of the usefulness of, and the opportunities presented by, this new vehicle; analyses the Regulation and the Directive; and examines the tax aspects of the SE. The second part reports on each of the Member States.